Novel Genetic and Cognitive Findings From the Long Life Family Study. (17th December 2021) - Wojczynski, Mary; Glynn, Nancy W; Hadley, Evan
Abstract: The Long Life Family Study (LLFS), funded by the National Institute on Aging, is an international collaborative study of the genetics and familial components of exceptional longevity and healthy aging. We phenotyped 4, 953 individuals from 539 two-generational families (1, 727 proband; 3, 226 offspring) at baseline (2006-2009). A second visit (2014-2017) was conducted for 2, 904 (478 proband; 2, 426 offspring) participants. The longitudinal, comprehensive in-person visits measured domains of healthy aging, including physical performance, cognition, and blood markers. Extensive genetic analyses were performed using the baseline blood draw, including genotyping with the Illumina 2.5M Human Omni array, linkage analyses with the families, whole genome sequencing using the TopMED protocol, and metabolomic assays. Collectively, this symposium will present novel findings that elucidate new potential genes and genetic interactions, investigate metabolomics profiles among APOE4 carriers, and refine phenotypic cognition definitions. Specifically, Dr. Santanasto will share results flanking the mesothelin gene associated with longitudinal gait speed. Then, Dr. An will share his findings of a new intronic variant in PKD1L2 gene associated with adiponectin, a marker of insulin resistance. Next, Dr. Arbeev will discuss genetic interactions between candidate genes for physiologic dysregulation and candidate genes for Alzheimer's disease (AD, UNC5C gene). Ms. Yao will examine metabolomic profile differences between APOE4 carriers who develop AD and those who do not. Lastly, Mr. Xiang will introduce a method for combining multiple cognitive tests into a more sensitive overall cognitive score. As Discussant, Dr. Evan Hadley will share insights and propose future directions for LLFS.